2016
DOI: 10.1371/journal.pbio.1002421
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor-Dependent Mutual Amplification between Netrin-1 and the Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) is an oncogenic virus associated with the onset of hepatocellular carcinoma (HCC). The present study investigated the possible link between HCV infection and Netrin-1, a ligand for dependence receptors that sustains tumorigenesis, in particular in inflammation-associated tumors. We show that Netrin-1 expression is significantly elevated in HCV+ liver biopsies compared to hepatitis B virus (HBV+) and uninfected samples. Furthermore, Netrin-1 was upregulated in all histological stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…In the early stages of the viral life cycle, HCV binding to its entry receptor complex, i.e., CD81 and claudin-1 (CLDN1), induces EGFR phosphorylation [54] and downstream signaling [55], thereby facilitating viral particle internalization. EGFR activity is prolonged by the NS5A-mediated alteration of EGFR trafficking [56] and by stimulated Netrin-1 expression, which impedes EGFR recycling [57]. Moreover, HCV replication itself promotes the expression of the receptor ligand EGF [58].…”
Section: Egf Signaling Pathwaymentioning
confidence: 99%
“…In the early stages of the viral life cycle, HCV binding to its entry receptor complex, i.e., CD81 and claudin-1 (CLDN1), induces EGFR phosphorylation [54] and downstream signaling [55], thereby facilitating viral particle internalization. EGFR activity is prolonged by the NS5A-mediated alteration of EGFR trafficking [56] and by stimulated Netrin-1 expression, which impedes EGFR recycling [57]. Moreover, HCV replication itself promotes the expression of the receptor ligand EGF [58].…”
Section: Egf Signaling Pathwaymentioning
confidence: 99%
“…Second, sh-UNC5A cells showed luminal/basal hybrid phenotype, and EGFR activation is common in cells with basal phenotype [ 48 ]. Third, a recent study showed that NTN1, in the absence of UNC5A, increases EGFR at the post-translational level [ 49 ]. We first measured EGFR levels in sh-Control and UNC5A knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many pathogens, including viruses, bacteria, and fungi, seem to have evolved the ability to exploit EGFR signaling to gain entry into host cells ( 33 ), and the mechanism of EGFR activation across these pathogenic microbes varies. For example, in the context of viral infection, hepatitis C virus increases signaling by disrupting EGFR recycling to enhance its surface expression ( 43 , 44 ). In contrast, the Campylobacter jejuni bacterium induces lipid raft formation, resulting in clustering and subsequent activation of EGFR ( 45 ), while meningitic Escherichia coli activates EGFR signaling by increasing sphingosine 1-phosphate (S1P 2 )-dependent release of heparin-binding ligand-like epidermal growth factor (HB-EGF) ( 35 ).…”
Section: Discussionmentioning
confidence: 99%